2015
DOI: 10.1038/onc.2015.186
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-induced senescence underlies the mutual exclusive nature of oncogenic KRAS and BRAF

Abstract: KRAS and BRAF are among the most commonly mutated oncogenes in human cancer that contribute to tumorigenesis in both distinct and overlapping tissues. However, KRAS and BRAF mutations are mutually exclusive; they never occur in the same tumor cell. The reason for the mutual exclusivity is unknown, but there are several possibilities. The two mutations could be functionally redundant and not create a selective advantage to tumor cells. Alternatively, they could be deleterious for the tumor cell and induce apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 26 publications
3
65
0
Order By: Relevance
“…Analysis by standard sensitivity sequencing has typically identified KRAS and BRAF mutations in a mutually exclusive fashion in CRC (4143). In order to explain these observations, it has been suggested that concomitant oncogenic activation of KRAS and BRAF would be counter-selected during tumorigenesis, as it would result in activation of cell-cycle inhibitory proteins of the Ink4/Arf locus, leading to oncogenic stress and senescence (44). Nevertheless, the use of more sensitive techniques, such as droplet digital PCR, have recently revealed that low-allele frequency KRAS mutations could coexist with BRAF V600E in CRC samples (7).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by standard sensitivity sequencing has typically identified KRAS and BRAF mutations in a mutually exclusive fashion in CRC (4143). In order to explain these observations, it has been suggested that concomitant oncogenic activation of KRAS and BRAF would be counter-selected during tumorigenesis, as it would result in activation of cell-cycle inhibitory proteins of the Ink4/Arf locus, leading to oncogenic stress and senescence (44). Nevertheless, the use of more sensitive techniques, such as droplet digital PCR, have recently revealed that low-allele frequency KRAS mutations could coexist with BRAF V600E in CRC samples (7).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, having two different MAPK pathway-activating mutations may confer a proliferative disadvantage. 45 A variety of approaches have been used to show that nevi are clonal, 16,4649 suggesting that the formation of nevi in humans occurs as a result of a single MAPK pathway-activating mutation in an individual melanocyte.…”
Section: Braf-activating Mutations Cause Nevus Formationmentioning
confidence: 99%
“…These factors are likely to include allele-specific attributes of oncogenic mutations in genes such as KRAS 36 and BRAF [36][37][38] ; the cell lineage in which the cancer has arisen 22,37,39 ; the levels of expression of mutant cancer genes 32,38,40,41 ; the co-existence of certain additional mutations 42 ;…”
Section: Discussionmentioning
confidence: 99%